Klasyfikacja dynamiczno-przestrzenna obiektów hierarchicznych z wykorzystaniem statystyk pozycyjnych - Strahl, Danuta; Markowska, Małgorzata (Dynamic and spatial classification of hierarchical objects using positional statistics, 2008)
The article presents a proposal of dynamic and structural construction of the measure, referring to hierarchical objects development, which includes: internal diversification of hierarchical objects with regard to the level of lower rank objects development, the level of hierarchical objects development in particular observation moments. The procedure of measure construction consists in two basic stages. The first stage includes the classification of lower rank objects, which are the components of hierarchical objects. The classification is based on positional statistics and presents a valuation nature. The second stage includes: the construction of structural measure referring to the development of hierarchical objects, applying weights assigned to classes of objects obtained in the first stage, in every moment of the study t = 1,2, ..., T, the construction of dynamic and structural hierarchical objects development measure in the overall study period from / = 1 to t = T . The last part of the article presents an empirical illustration of the suggested procedure for 25 EU member countries and 254 NUTS-2 level regions representing European regional space.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 16-27